Polish Independent Press Summary, no. 1 (1987) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
A digest of Polish underground press (including articles, tables of content, and book covers) compiled by members of the RFE Polish Underground Publications Unit to be used in a daily 20-minute broadcast on Polish samizdat. Extract from Przegląd Wiadomości Agencyjnych, no. 28 (26 August 1987). Extract from Przegląd Wiadomości Agencyjnych, no. 29 (2 September 1987). Extract from Portowiec, no. 108 (23 August 1987). Table of Contents from Polityka Polska, no. 9 (March 1987). Table of Contents from Vacat, no. 45 (June 1987). Extract from Praworządność: Pismo o Prawie i Bezprawiu, no. 17 (1987).